Penerapan Asuhan Kesehatan Gigi Dan Mulut Pada Lansia Di Panti Sosial Tresna Werdha Budi Mulia 1 Jakarta Timur - Afif Afandy Hasanudin; Syaifia Putri, Rifa Fauziah; Setyawati , Baby Prabowo; Setyowati, Julia Dance; Ichwan, Viennie Adzkia (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Introduction: The application of dental and oral health care is the provision of planned dental and oral health care services, aimed at certain groups with a certain period of time to get optimal results. The application of care in this study was carried out to the elderly, namely by seeing if there was a change in the debris index score with teeth brushing skills before and after counseling. The application of dental and oral health care will be more effective if there are counseling activities on how to care for and maintain dental and oral hygiene. Research objectives: This study aims to analyze the application of dental and oral health care with the application of dental brushing skills and debris index scores before and after counseling. Research method: This type of research uses quantitative methods to master phenomena in a scientific social context with the phenomenon being studied. The sample in this study used a quota sampling technique of 30 elderly people who met the requirements as a sample from the population by checking the debris index and filling out a questionnaire on brushing skills before and after counseling using power point media. Research Results: This study uses the wilcoxon test. The results of the analysis showed that the pre test and post test of tooth brushing skills in Asymp. Sig. (2-tailed) 0.000 (<0.05) and debris index 0.000 (<0.05). The results of the average statistical test of the difference before and after the counseling of brushing skills were 15.5. Before and after the inspection of the debris index 15.5. Conclusion: There are differences before and after the debris index examination and tooth brushing skills after counseling.